Pengaruh Kepatuhan Wajib Pajak dan Sanksi Pajak Terhadap Penerimaan Pajak Bumi dan Bangunan di Kota Tangerang Selatan Tahun 2019-2023 - Putri, Anthiana Meilia; Ngatimin, Ngatimin (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2025)
This study aims to analyze the effect of taxpayer compliance and tax sanctions on Land and Building Tax (PBB) revenue in South Tangerang City during the 2019–2023 period. The independent variables in this study are taxpayer compliance and tax sanctions, while the dependent variable is Land and Building Tax revenue. The research employed a quantitative method with panel data regression analysis. The sample was determined using purposive sampling, consisting of 5 districts that met the criteria over 5 years, resulting in 25 observations. The data used are secondary data obtained from the Regional Revenue Agency of South Tangerang City. The findings reveal that taxpayer compliance does not have a significant effect on Land and Building Tax revenue. On the other hand, tax sanctions have a significant effect on Land and Building Tax revenue. Simultaneously, taxpayer compliance and tax sanctions significantly influence Land and Building Tax revenue in South Tangerang City. This study highlights that tax sanctions play an important role in enhancing actual taxpayer compliance, thereby contributing to the increase in Land and Building Tax revenue.